Rapid Phenotypic Antibiotic Susceptibility Testing of Uropathogens Using Optical Signal Analysis on the Nanowell Slide - Veses-Garcia, Marta; Antypas, Haris; Löffler, Susanne; Brauner, Annelie; Andersson-Svahn, Helene; Richter-Dahlfors, Agneta (Frontiers in Microbiology, 2018)
Achieving fast antimicrobial susceptibility results is a primary goal in the fight against antimicrobial resistance. Standard antimicrobial susceptibility testing (AST) takes, however, at least a day from patient sample to susceptibility profile. Here, we developed and clinically validated a rapid phenotypic AST based on a miniaturized nanotiter plate, the nanowell slide, that holds 672 wells in a 500 nl format for bacterial cultivation. The multitude of nanowells allows multiplexing with a panel of six antibiotics relevant for urinary tract infections. Inclusion of seven concentrations per antibiotic plus technical replicates enabled us to determine a precise minimum inhibitory concentration for 70 clinical uropathogenic Escherichia coli isolates. By combining optical recordings of bacterial growth with an algorithm for optical signal analysis, we calculated Tlag, the point of transition from lag to exponential phase, in each nanoculture. Algorithm-assisted analysis determined antibiotic susceptibility as early as 3 h 40 min. In comparison to standard disc diffusion assays, the nanowell AST showed a total categorical agreement of 97.9 % with 2.6 % major errors and 0 % very major errors for all isolate-antibiotic combination tested. Taking advantage of the optical compatibility of the nanowell slide, we performed microscopy to illustrate its potential in defining susceptibility profiles based on bacterial morphotyping. The excellent clinical performance of the nanowell AST, combined with a short detection time, morphotyping, and the very low consumption of reagents clearly show the advantage of this phenotypic AST as a diagnostic tool in a clinical setting.